Two theorems on closeness of the set of Laplace-type transformations - Safaryan, R. G. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
We formulate and prove two theorems on the limit of the Laplace transformations for random variables with values in the space of nonnegative measures.